A retrospective on: MNC knowledge transfer, subsidiary absorptive capacity, and HRM - Minbaeva, Dana B; Pedersen, Torben; Björkman, Ingmar; Fey, Carl F (Journal of International Business Studies, 2014)
In this retrospective, we revisit the goals of the original paper, and we review the studies that have used our paper to discuss the “concept” and the “development” of absorptive capacity. We also propose directions for future research, stressing the need to develop thorough theoretical and empirical models of absorptive capacity as a multi-level and dynamic construct that is contingent on the context in which it is embedded.